Are Monthly Seasonals Real? A Three Century Perspective - Zhang, Cherry Y.; Jacobsen, Ben (Review of Finance, 2013)
Over 300 years of UK stock returns reveal that well-known monthly seasonals are sample specific. For instance, the January effect only emerges around 1830. Most months have had their 50 years of fame, showing the importance of long time series to safeguard against sample selection bias, noise, and data snooping. The overall conclusion is that monthly seasonals might simply be in the eye of the beholder.